Reading habit and students’ attitudes towards reading: a study of students in the faculty of education UiTM Puncak Alam / Jamiah Baba and Faiza Rostam Affendi - Baba, Jamiah; Affendi, Faiza Rostam (Universiti Teknologi MARA, 2020)
Ability to read is crucial as reading affects intellectual and emotional growth of an individual. Those who read well have more chances in widening their mental horizons and better opportunities of success. Hence, this paper is an attempt to understand the reading habits and attitudes of the students in the Faculty of Education in Universiti Teknologi Mara, Puncak Alam. To collect the relevant data, a questionnaire was designed and distributed to 80 students. The questionnaire investigated the students’ reading habit, preferences, and attitudes towards reading. The research findings through quantitative analysis revealed that the students had an overall positive attitude towards academic and leisure reading as they read academically and leisurely daily or at least once a week. Apart from that, digital materials are considered better compared to printed texts when it comes to the students’ preference and its availability. Based on the findings, several recommendations were made to help improve students’ reading habits and attitudes. Having a national survey on Malaysian students’ reading habits is deemed necessary as it can document current trends (including the use of digital materials as a form of reading) and factors affecting students’ reading habits and attitudes so that more fruitful actions to improve students’ reading habits can be taken. Finally, teachers should also play a more significant role in motivating students to read as the findings yield that teachers are shown to have an impact on students’ reading habits and attitudes.